Primary School Teachers’ Perceptions of Critical Literacy in EFL Classrooms - Hidayat, Raden Aulia Utami; Setyaarini, Sri; Gustine, Gin Gin; Hermawan, Budi (Mimbar Sekolah Dasar, 2024)
Critical literacy has become an essential approach in education, yet research on its perception and implementation at the primary school level, particularly in EFL contexts, still needs to be completed. This study examines primary school teachers' perceptions of critical literacy in English as a Foreign Language (EFL) classroom in West Java. Using a mixed-methods approach, data were collected from 50 primary school teachers through structured surveys and open-ended questionnaires. Quantitative data were analyzed using descriptive statistics, while qualitative responses were analyzed thematically. Findings indicate a limited understanding of critical literacy, although teachers are strongly willing to incorporate it into their teaching. Key challenges include inadequate professional development, insufficient resources, and rigid curriculum constraints, emphasizing the need for targeted training to enhance students' learning experiences. Limitations include the small sample size and focus on one region. Future research should explore broader contexts and the longitudinal impacts of critical literacy practices. However, it is still expected that the study could give primary school teachers insight into critical literacy as one of the approaches in education.